pola dan perkembangan permukiman di Kecamatan Mandiangin Koto Selayan Kota Bukittingi - riyan haylan24; syafri anwar; yudi antomi (JURNAL BUANA, 2019)
This study aims to determine the settlement patterns of 2006-2017 and the development of settlements in the Mandiangin District of Koto Selayan, Bukittinggi City. This type of research is quantitative descriptive. The population in this study was Mandiangin Koto Selayan District and the sample in this study was a settlement in the Mandiangin District of Koto Selayan. Analysis using the closest neighbor method with the help of ArcGIS 10.1 software. The results in this study are, 1. 2006 settlement patterns, Nearest Neighbor Ratio 1.020039 with Expected Mean Distance of 180.164770 and z-score -0.392828 T interval (nearest neighbor index) between 0.7 to 1.4. This shows that the distribution of settlements in Mandiangin Koto Selayan District is random. 2. 2017 settlement patterns, Nearest Neighbor Ratio 1.725348 with Expected Mean Distance 378.264177 and z-score -5,550569 T intervals (nearest neighbor index) between 1.4 to 2.15. This shows that the distribution of settlements in the Mandiangin District of Koto Selayan is dispersed. 3. Development of settlements in 2006-2017 in the Mandiangin District of Koto Selayan, which is 3,238,123m2. Keywords: Settlement Patterns, Development of Settlements